2014
DOI: 10.1093/ntr/ntu062
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Pictorial Health Warnings in Mauritius: Findings From the ITC Mauritius Survey

Abstract: introduction: Health warnings on tobacco packages are an effective strategy for informing the public about the harms associated with tobacco use. Most studies investigating the effectiveness of pictorial health warnings (PHWs) on cigarette packages are from high-income countries. This study evaluated the impact of PHWs on smokers' perceptions and behavior in Mauritius, the first country in the World Health Organization African region to implement PHWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
4
32
0
Order By: Relevance
“…We found that warning salience and cognitive responses decreased in these countries. This pattern of decreases of self-reported warning label responses (warning label ‘wear-out’) has been reported before 14 15 25. We found that warning avoidance increased in Germany, but avoidance remained much lower (6% tried to avoid labels in the past month at the second survey wave) than in France (17%) and the UK (18%) after the implementation of pictorial warning labels.…”
Section: Discussionsupporting
confidence: 77%
“…We found that warning salience and cognitive responses decreased in these countries. This pattern of decreases of self-reported warning label responses (warning label ‘wear-out’) has been reported before 14 15 25. We found that warning avoidance increased in Germany, but avoidance remained much lower (6% tried to avoid labels in the past month at the second survey wave) than in France (17%) and the UK (18%) after the implementation of pictorial warning labels.…”
Section: Discussionsupporting
confidence: 77%
“…6 Health warnings constitute a powerful intervention for increasing knowledge about the specific harms of tobacco use 7 and for increasing thoughts and motivations to quit smoking among smokers in many countries including Thailand, Malaysia, Uruguay, Mauritius, Mexico, Australia and Canada. [8][9][10][11][12][13][14] Health warnings also have the potential to prevent smoking initiation among nonsmokers, including youth. 15 Smokers rate health warnings on cigarette packages as a prominent and credible source of information about the harms of tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…About one-quarter of smokers (29.7%) and dual users (20.6%) noticed the warnings-which is much lower than the percentage of smokers who noticed warnings in Australia (52.0%) and China (43.1%) at the time when these two countries had text-only warnings of a similar size as Japan's current warnings; and in the United Kingdom (44.0%) at the time when they had text-only warnings that were even smaller than Japan's current warnings [40,45]. The weak salience of Japan's text-only warnings is even more pronounced when compared to significant increases in smokers' noticing of warnings following the change from text-only to pictorial warnings in other countries, such as Malaysia (54 to 67%) [40], Thailand (62 to 70%) [46], and Mauritius (58 to 83%) [42].…”
Section: Discussionmentioning
confidence: 96%
“…But a more likely outcome over time is that the effectiveness of Japan's warnings would actually decrease because of the known phenomenon of "warning wear-out"-warnings become less effective over repeated exposures. ITC studies have documented warning wear-out in several countries, including Canada and the United States [61] and Mauritius [42]. Longitudinal studies would also be valuable to measure the likely increase in health warning effectiveness if Japan's text-only warnings are replaced with pictorial warnings, as called for by the WHO FCTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation